Efficacy and Mechanism of Electroacupuncture Treatment of Rabbits With Different Degrees of Knee Osteoarthritis: A Study Based on Synovial Innate Immune Response - Ruan, Anmin; Wang, Qingfu; Ma, Yufeng; Zhang, Dong; Yang, Lili; Wang, Zhongpeng; Xie, Qi; Yin, Yueshan (Frontiers in Physiology, 2021)
Knee osteoarthritis (KOA) is a chronic degenerative bone and joint disease, which is often clinically manifested as pain, joint swelling, and deformity. Its pathological manifestations are mainly synovial inflammation and cartilage degeneration. This study aims to investigate the efficacy of electro-acupuncture (EA) on model rabbits with varying degrees of KOA and to study the mechanism of EA on KOA based on the innate immune response. Mild and moderate rabbit KOA models were established using a modified Hluth method, and EA was given to both the mild and moderate model groups. The Lequesne-MG index was used to evaluate the behavioral changes in the rabbits before and after EA treatment. Morphological changes in the synovial membrane and cartilage of each group were observed by H&E staining. The Mankin scoring standard and the Krenn scoring standard were used to score the pathology of the cartilage tissue and synovial tissue, respectively. The inflammatory factors and metalloproteinases were detected in the serum of each group by ELISA. The protein and messenger RNA (mRNA) expressions of important elements related to Toll-like receptors (TLRs)-mediated innate immune response in the synovial tissue were detected by Western blot and quantitative PCR (qPCR). The Lequesne-MG index score of the rabbits gradually increased with the modeling prolonged but decreased significantly after EA treatment, indicating that EA has a better effect on alleviating the pain and improving the dysfunction. The morphological analysis showed that the inflammation of and the damage to the synovial membrane and the cartilage tissue gradually deteriorated with the modeling prolonged. However, the synovial membrane inflammation was significantly relieved after EA treatment, and the cartilage injury showed signs of repair. The ELISA analysis showed that, with the modeling prolonged, the serum-related inflammatory factors and mechanism of metalloproteinases gradually increased but decreased after EA treatment. The tumor necrosis factor alpha (TNF-α), interleukin 6 (IL-6), and matrix metalloproteinase3 (MMP3) of EA1 group were significantly lower than those of EA2 group. Both Western blot and qPCR results showed that the protein and mRNA expressions of the elements related to the innate immune response in the synovial membrane increased gradually with the modeling prolonged, but decreased significantly after EA treatment. Additionally, the expression of some components in EA1 group was significantly lower than that in EA2 group. These results confirm that synovial inflammation gradually aggravated with time from the early to mid-stage of KOA. EA alleviated the inflammation and histological changes in KOA rabbits by inhibiting the TLRs-mediated innate synovial immune response. This suggests that using EA in the early stage of KOA may achieve a desirable efficacy.